Cavity Enhancement of single quantum dot emission in the blue - Taylor, R; Jarjour, A; Collins, D; Holmes, M; Oliver, R; Kappers, M; Humphreys, C (2010)
Cavity-enhanced single-photon emission in the blue spectral region was measured from single InGaN/GaN quantum dots. The low-Q microcavities used were characterized using micro-reflectance spectroscopy where the source was the enhanced blue output from a photonic crystal fibre. Micro-photoluminescence was observed from several cavities and found to be ~10 times stronger than typical InGaN quantum dot emission without a cavity. The measurements were performed using non-linear excitation spectroscopy in order to suppress the background emission from the underlying wetting layer. © The Author(s) 2009.